Wireless communication-based state estimation of automotive aftertreatment systems. (August 2017) - Motroniuk, Iurii; Królak, Radoslaw; Stöber, Ralf; Fischerauer, Gerhard
Highlights: Method for the non-destructive, in-situ monitoring of catalytic-system states. Based on small-size, cost-effective communication-system hardware and software. Potentially applicable to serial automotive aftertreatment systems. Also suitable for industrial installations. Abstract: We propose a novel approach for a cheap and easy implementable microwave-based system for the state determination of emission control and exhaust gas aftertreatment systems in motor vehicles, trucks, combustion installations, and similar equipment. It is particularly important to monitor the state of diesel particulate filters (DPF), three-way catalytic converters (TWC), and selective catalytic reduction (SCR) catalysts. It is proposed to consider the volume inside the housing of the DPF, TWC, or SCR as a communications channel between two terminals of a wireless communications system. From the transmission channel characteristics, the properties of the catalyst, such as the catalyst state, can be estimated. Measurement results for both soot-loaded and empty DPFs are presented. The technique involves a small-size and cost-effective modular architecture and has the potential for serial application.